2010
DOI: 10.1097/sap.0b013e3181b0273c
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma (PRP) Promotes Survival of Fat-Grafts in Rats

Abstract: This study evaluated the effects of platelet-rich plasma (PRP) on resorption and adipocyte survival in autologous fat-graft of rats prepared with isogenous PRP. Fat grafts prepared without PRP (control group) became united to the tissue adjacent to the implantation site and were significantly resorbed from 30 days. On the other hand, fat grafts prepared with PRP (PRP group) demonstrated little resorption from 30 to 120 days and appeared pink, had a soft, supple feel, and were easily compressible. Histologic se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 26 publications
3
61
2
1
Order By: Relevance
“…The mixture was implanted on a dorsal subcutaneous pocket. 22 The results showed similar histology between the PRP and control groups 10 days postoperatively; however, the control group expectedly had fewer normal adipocytes at 20 days postoperatively and the PRP group had more granulation tissue and capillary formation and good maintenance of normal adipocytes for at least 120 days. Oh et al mixed human lipoaspirated fat graft and activated PRP (by thrombin and CaCl 2 ) at a ratio of 7:2 and implanted it on the scalps of nude mice.…”
Section: Preclinical Studiessupporting
confidence: 51%
See 1 more Smart Citation
“…The mixture was implanted on a dorsal subcutaneous pocket. 22 The results showed similar histology between the PRP and control groups 10 days postoperatively; however, the control group expectedly had fewer normal adipocytes at 20 days postoperatively and the PRP group had more granulation tissue and capillary formation and good maintenance of normal adipocytes for at least 120 days. Oh et al mixed human lipoaspirated fat graft and activated PRP (by thrombin and CaCl 2 ) at a ratio of 7:2 and implanted it on the scalps of nude mice.…”
Section: Preclinical Studiessupporting
confidence: 51%
“…Although some successful clinical results were reported, 16,17 evidence supporting the application of PRP combined with fat grafts in soft tissue augmentation remains limited, as only a few basic research and preclinical studies in small animals have been conducted. 15,[18][19][20][21][22][23] Furthermore, no details on molecular mechanisms are addressed in the literature. In this review article, we discuss the possible molecular mechanisms of PRP in fat graft survival based on a review of the current literature.…”
Section: Introductionmentioning
confidence: 99%
“…We looked at similar parameters in our study, and found that the normal adipocyte area and number of mature vessels were significantly higher in the PRP+fat group (Group 2). However, in contrast to Nakamura et al [28] , we found significantly lower values in the PRP+fat group compared to Group 1 with regard to the granulation tissue area and vacuolization area parameters. We believe that this may have been due to differences in the areas where the grafts were placed (tympanic membrane vs. subcutaneous dorsal pocket).…”
Section: Discussioncontrasting
confidence: 56%
“…PRP prevents fat graft resorption, and it showed positive effects on the success of the fat graft. Nakamura et al [28] created subcutaneous dorsal pockets in their empirical study on rats to show the effects of PRP on fat graft resorption. This study involved two groups, where a fat graft was placed on its own or in combination with PRP.…”
Section: Discussionmentioning
confidence: 99%
“…PRP, after being activated, releases large amounts of growth factors and cytokines, stimulating increased cell replication, increased collagen production, recruitment of other cells to the site of injury, stimulating neoangiogenesis and differentiation induction 5 . In animal studies 22,23 the association of fat with PRP increased graft take, whereas Por et al 24 observed that this association is not beneficial for increasing the viability of the grafts. In the latter work, there is no mention of the PRP activation, a fact that may have contributed to the absence of benefits of PRP on the viability of the grafted fat.…”
Section: Discussionmentioning
confidence: 99%